Biodegradable Gold Nanovesicles with an Ultrastrong Plasmonic Coupling Effect for Photoacoustic Imaging and Photothermal Therapy1. Issue 52 (6th December 2013) - Huang, Peng; Lin, Jing; Li, Wanwan; Rong, Pengfei; Wang, Zhe; Wang, Shouju; Wang, Xiaoping; Sun, Xiaolian; Aronova, Maria; Niu, Gang; Leapman, Richard D.; Nie, Zhihong; et al.
Abstract The hierarchical assembly of gold nanoparticles (GNPs) allows the localized surface plasmon resonance peaks to be engineered to the near‐infrared (NIR) region for enhanced photothermal therapy (PTT). Herein we report a novel theranostic platform based on biodegradable plasmonic gold nanovesicles for photoacoustic (PA) imaging and PTT. The disulfide bond at the terminus of a PEG‐b‐PCL block‐copolymer graft enables dense packing of GNPs during the assembly process and induces ultrastrong plasmonic coupling between adjacent GNPs. The strong NIR absorption induced by plasmon coupling and very high photothermal conversion efficiency (η=37 %) enable simultaneous thermal/PA imaging and enhanced PTT efficacy with improved clearance of the dissociated particles after the completion of PTT. The assembly of various nanocrystals with tailored optical, magnetic, and electronic properties into vesicle architectures opens new possibilities for the construction of multifunctional biodegradable platforms for biomedical applications.